Gender Analysis in Indonesia's Legislation Regarding Political Laws - Erlina Erlina; Nika Normadilla (University of Jember, 2020)
This paper examines Indonesia's current legislation on politics, inter alia, Political Parties Law, Election Law, and Parliament Law, by using gender analysis. This paper considers how these laws ensure equitable access, participation, control, and benefits for men and women. Under the justice and gender equality approach, these laws are not optimal, especially under the control and benefit indicators. In this context, Political Parties Law contributes more to the indicator of access, while Electoral Law provides access and participation indicators. At the same time, Parliament Law is expected to contribute the most to the control and benefit indicators. However, it is regrettable that Parliament Law does not comply with these two indicators. Also, the Constitutional Court's interpretation was not followed in a series of legislative revisions of Parliament Law. Therefore, the gender approach in the legislative revision of these three laws should be encouraged to benefit from social life with more just and non-discriminatory. It should also provide equal opportunity for every citizen to gain access, participatory rights, control, and benefits in development. Hence, it is inevitable to the importance of the government commitment in gender mainstreaming in policy, harmonization, and synchronization of laws and regulations. KEYWORDS: gender justice and equality, political laws, women's representation.